Energy efficiency maximisation for WPCN with distributed massive MIMO system. Issue 19 (1st September 2016) - Kim, W.; Yoon, W.
Abstract : A joint time allocation and energy beamforming method for the maximisation of the system energy efficiency (EE) in multi‐user multi‐cell wireless powered communication network (WPCN) with distributed massive multi‐input multi‐output (DM‐MIMO) system is proposed. An iterative algorithm to solve the EE maximisation problem is proposed. The simulation results show that the proposed scheme can achieve a significant EE gain. Further, it reveals that the achievable sum capacity of the DM‐MIMO is considerably higher than that of a conventional centralised massive multi‐input multi‐output system.